KONVERSI BUDAYA ANIMISME PADA NILAI-NILAI KEISLAMAN “SEDEKAH BUMI DI MAKAM MBAH BUYUT” DALAM KEBIJAKAN PERATURAN ADAT PEMERINTAH DESA TLANAK KEDUNGPRING - Nur Iftitahul Husniyah (CENDEKIA: Jurnal Studi Keislaman, 2020)
Javanese society is still very thick with the animist tradition of believing in ancestral spirits. It is said that the ancestors according to community culture were the first people to set foot in a settlement or village. Although at this time the ancestors had been buried either in a field or under a large tree that was more than hundreds of years old but his spirit was believed to still be able to protect the surrounding community in quotes is the grandchildren of great-grandfather. Many stories say that by respecting the spirits of the ancestors, the Tlanak villagers often get blessings, for example recovering from illness, high status, and good fortune. So the Tlanak village government stipulates that once a year the people of Tlanak village must celebrate respect for the spirits of the ancestors, called the alms of the earth at the grave of great-grandfather. The budget has been set by the village and each Head of the Tlanak village community is also obliged to pay the dues that have been determined by the village government. However, the development of the great alms culture of the great-grandmother has now begun to shift, that is, entering Islamic values ​​and culture. This paper explores the common thread between animism culture in the form of respect for ancestral spirits and Islamic culture as outlined in the policy of the Tlanak village government in Lamongan